2023
DOI: 10.2147/jpr.s411923
|View full text |Cite
|
Sign up to set email alerts
|

Skin Temperature of Acupoints in Health and Primary Dysmenorrhea Patients: A Systematic Review and Meta-Analysis

Abstract: Objective Dysmenorrhea is a common clinical condition and some studies shown that the skin temperature of some acupoints changes in primary dysmenorrhea (PD) patients. This study aimed to evaluate the changes in skin temperature at specific acupoints in PD patients and healthy subjects. Methods The literature for assessing skin temperature at acupoints in PD patients and healthy subjects was searched in eight databases. The literatures obtained from the search was indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Cited reference Author and publication year acupoint skin temperature between patients and the general population, the temperature difference between the unaffected and affected sides or the temperature difference in the patient's own treatment (Liu et al, 2020;Li et al, 2021;Reddy et al, 2023;Tu et al, 2023;Wang et al, 2023). An article published in 2012 shows asthma patients had significantly lower overall infrared radiation intensity at the left Taiyuan (LU 9) than that of healthy volunteers which suggested that IRT detection of acupoint temperature has a potential role in the diagnosis of diseases (Zhou et al, 2012).…”
Section: Rank Co-citation Countsmentioning
confidence: 99%
“…Cited reference Author and publication year acupoint skin temperature between patients and the general population, the temperature difference between the unaffected and affected sides or the temperature difference in the patient's own treatment (Liu et al, 2020;Li et al, 2021;Reddy et al, 2023;Tu et al, 2023;Wang et al, 2023). An article published in 2012 shows asthma patients had significantly lower overall infrared radiation intensity at the left Taiyuan (LU 9) than that of healthy volunteers which suggested that IRT detection of acupoint temperature has a potential role in the diagnosis of diseases (Zhou et al, 2012).…”
Section: Rank Co-citation Countsmentioning
confidence: 99%
“…For example, the method of determining skin electrical resistance was utilized to reveal that Ryodoraku is comparable to the meridians, i.e., it uses electrical characteristics ( Lee et al, 2005 ). Similarly, our team employed infrared thermography to determine skin temperature at the relevant acupoints and some differences in skin temperature, i.e., thermal characteristics were discovered ( Fan et al, 2022 ; Wang et al, 2023 ). Furthermore, the meridians have optical characteristics ( Yang et al, 2007 ) and sound characteristics ( Xiong et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%